Child Migration in Africa - Hashim, Iman (Africa Now, 2011)
Child Migration in Africa explores the mobility of children without their parents within West Africa. Drawing on the experiences of children from rural Burkina Faso and Ghana, the book provides rich material on the circumstances of children's voluntary migration and their experiences of it. Their accounts challenge the normative ideals of what a 'good' childhood is, which often underlie public debates about children's migration, education and work in developing countries. The comparative study of Burkina Faso and Ghana highlights that social networks operate in ways that can be both enabling and constraining for young migrants, as can cultural views on age- and gender-appropriate behaviour. The book questions easily made assumptions regarding children's experiences when migrating independently of their parents and, by drawing parallels with children's migration in Latin America and Asia, contributes to analytical and cross-cultural understandings of childhood. Part of the groundbreaking Africa Now series, Child Migration in Africa is an important and timely contribution to an under-researched area.